THE THEME OF CHALLENGES AND DIFFICULTIES FACED BY INDIAN IMMIGRANTS IN CANADA IN RUPI KAUR'S POEM BROKEN ENGLISH (2022) - Fadilah Pertiwi, Annisa; Widisanti, Ni Made; Kristyowati, Dyah (Universitas Pakuan, 2024)
The research focuses on the challenges and difficulties faced by Indian immigrants in Canada, as portrayed in the poem ‘Broken English’ by Rupi Kaur. The study analyzes the intrinsic elements of the poem, including theme, feeling, message, diction, rhyme and rhythm, typography, imagery, symbol, and figurative language, along with the extrinsic elements of biography and meaning. Qualitative methods are employed to analyze data on Indian immigrant issues. The expressive approach is utilized for analyzing poetry and implicit meaning. According to research, Rupi Kaur’s “Broken English” revolves around the challenges faced by Indian immigrants in Canada. The second generation of Indian immigrants encounter a range of difficulties in adjusting to a new environment, including economic hardship and discrimination due to their non-native English proficiency. They also experience the consequences of discrimination that their parents faced, such as being denied recognition as Indian immigrants in Canada due to their thick accents. Furthermore, some second-generation Indian immigrants may discriminate against their fellow Indian immigrants.